Repositioning Mosques as Centers for Islamic Socio-Economic Empowerment: Lessons from the Jogokariyan Mosque in Indonesia - Fauziyah, Nurul; Abdy, Kamaruddin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
Mosques have historically functioned not only as places of worship but also as centers for social, educational, and economic development within Muslim communities. However, in contemporary contexts, particularly in Indonesia, the socio-economic role of many mosques has declined and remains underutilized. This study aims to analyze strategies for repositioning mosques as centers of Islamic socio-economic empowerment by examining the best practices implemented at the Jogokariyan Mosque in Yogyakarta, Indonesia. This research employs a qualitative document analysis method, utilizing secondary data obtained from scientific literature, journal articles, institutional reports, and previous empirical studies related to mosque management and community empowerment. The findings indicate that effective mosque-based empowerment is strongly supported by professional management practices grounded in the POAC (Planning, Organizing, Actuating, and Controlling) framework, transparent financial governance, and a balanced allocation of consumptive and productive funds. The Jogokariyan Mosque exemplifies successful community engagement through innovative programs, including waste banks, community marketplaces, daily almsgiving initiatives, social services, and publicly accessible financial reporting. Active participation of congregants and inclusive leadership by mosque administrators (takmir) further strengthens the sustainability of these programs. This study concludes that mosques can function as dynamic institutions for socio-economic development when managed transparently, participatorily, and adaptively. The Jogokariyan model offers a replicable framework for other mosques in Indonesia to enhance their role in addressing community welfare and economic resilience.